2009
DOI: 10.1007/s11270-009-9982-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Table Level on Metal Mobility at Different Depths in Wetland Soils of the Scheldt Estuary (Belgium)

Abstract: An experiment was set up to assess the factors affecting metal mobility in five wetland soils of the Scheldt estuary at different sampling depths when subjecting the soils to various water table levels. Pore water metal concentrations were monitored for 10 months at four sampling depths (10, 30, 60 and 90 cm) upon adjusting the water table level to 0, 40 and 80 cm below the surface of the soils. Nickel (Ni) release is facilitated by reductive conditions. These reductive conditions mainly occur below the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…3) could be caused by sulphide precipitation, as also found by other authors (Carbonell et al, 1999;Koretsky et al, 2007;Schröder et al, 2008;Van der Geest and Paumen, 2008;Du Laing et al, 2007, 2009a. The dark colour and the typical odour suggest that sulphides were formed in the MCs at reducing conditions in our experiment.…”
Section: Fate Of CD Cu Ni and Znsupporting
confidence: 86%
See 2 more Smart Citations
“…3) could be caused by sulphide precipitation, as also found by other authors (Carbonell et al, 1999;Koretsky et al, 2007;Schröder et al, 2008;Van der Geest and Paumen, 2008;Du Laing et al, 2007, 2009a. The dark colour and the typical odour suggest that sulphides were formed in the MCs at reducing conditions in our experiment.…”
Section: Fate Of CD Cu Ni and Znsupporting
confidence: 86%
“…On the other hand, elements such as As can also be immobilized due to co-precipitation with or adsorption to Fe and Mn (hydr)oxides under oxic conditions. Moreover, divalent metal immobilization can be induced under anoxic conditions due to the presence of hardly soluble sulphides (Van Griethuysen et al, 2005;Du Laing et al, 2007, 2009a. Brümmer (1974) mentioned that sulphides are generated from sulphates below E H −50 mV at pH 7 (corresponds to E H 68 mV at pH 5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Mn and Zn this ratio ranged between 25 and 45 %, while for Cu and Pb it was of around 20 %. Previous works have shown that Cd and to a lesser extent Cu and Zn are more available under high-salinity conditions (Du Laing et al 2009a). …”
Section: Influence Of Soil Parameters On Plant Colonizationmentioning
confidence: 94%
“…Only few studies report on the effects of reduction with respect to metal mobility and emissions to surrounding groundwater systems. There are some useful studies that include field or laboratory measurements (e.g., Han et al 2001;Burton et al 2008;Du Laing et al 2009), and also modelling studies that use a thermodynamic approach have been reported (e.g., De Rooij and Gerrits 1995; Griffioen et al 2006). However, the outcomes of the measurements in the field and modelling studies are not always in agreement, indicating that the uncertainty around soil inundation or sediment storage is still large.…”
Section: Introductionmentioning
confidence: 99%